On Receiving Asylum Seekers: Identity working as a process of material-discursive interpellation. Issue 9 (September 2019) - Hultin, Lotta; Introna, Lucas
This paper responds to recent calls to study how materiality is implicated in the process of subject positioning by grounding itself in a relational and performative ontology. By situating our analysis in Barad's post-humanist view of discourse as material-discursive practice, and by drawing on the concepts of interpellation and hailing, we show how material-discursive practices at three different service sites of the Swedish Migration Board are profoundly constitutive of the manner in which asylum seekers and officers become hailed into various subject positions. In so doing, our study contributes to the development of a post-humanist understanding of how subject positions are enacted and governed within organizations. More precisely, we move beyond the conception of the intentional human and the non-intentional non-human in order to foreground the manner in which mundane material-discursive practices always and already condition (or govern) the possibilities for subjects (and objects) to be and to act, specifically and immanently. Thus we suggest that matter and soul are intertwined in ways that make their separation less convincing, if tenable at all.